Effectiveness of Advanced Organizer Learning Strategies on the Achievement of Fiqh with Varied Cognitive Styles - Mufidah, Luk-Luk Nur (Letiges, 2024)
This study aimed to ascertain the treatment variable's primary influence and interaction effect on learning achievement in the Fiqh course. This study used a quasi-experimental approach, namely the nonequivalent control group design. The participants of the study were divided into two classes, namely Class A and Class B. A random process is conducted in the selection of the study subject class. In contrast, allocating students within each class is considered a fixed entity (intact group) that cannot be altered. The gathered data underwent statistical inference processing utilizing the two-lane 2x2 variant analysis technique. The findings indicated significant variations in learning outcomes in Fiqh courses between two groups of students instructed using different advanced organizer strategies, namely mind maps and concept maps. Additionally, no significant disparity in student achievement in Fiqh courses was observed between students with field dependence and field independence cognitive styles. Furthermore, no interaction effect was found between the learning strategies of advanced organizer types (mind maps and concept maps) and field dependence and field independence cognitive styles on learning achievement in Fiqh courses. The descriptive statistics analysis indicates that implementing the mind map advance organizer strategy (mean 78.59) exhibits a higher level of effectiveness than the concept map advance organizer strategy (mean 67.61) in enhancing student academic performance. It can be inferred that the advanced organizer technique known as the mind map type is consistently more effective than the concept map type, irrespective of variations in cognitive styles. In essence, using mind maps as an advanced organizer by students renders the consideration of cognitive style unnecessary, as it does not exert a differential impact on enhancing academic performance.